Estimates of Uterine Rupture Bad Outcomes Using Propensity Score and Determinants of Uterine Rupture in Mizan-Tepi University Teaching Hospital: Case Control Study - Tegene Legese Dadi; Teklemariam Ergat Yarinbab (Hindawi Limited, 2017)
Background. Uterine rupture is a tear in the wall of uterus which carries grave risks to the mother as well as her baby. Objectives. To estimate uterine rupture bad outcomes using propensity score and its determinants in Mizan-Tepi University teaching hospital. Methods. A case control study on 363 participants, 121 cases and 242 controls, was conducted. Data was analyzed by STATA 14. Propensity score matching analysis was used to see causes. Level of significance of p value is ≤0.05. Results. Females who reside in rural areas (AOR = 3.996; 95% CI: 2.011, 7.940) are at higher risk of acquiring uterine rupture. Females who had ANC follow-up (AOR = 0.315; 95% CI: 0.164, 0.606) and preterm gestational age (AOR = 0.135; 95% CI: 0.025, 0.725) are at lower risk of developing uterine rupture. Propensity score matching analysis shows that, from 100 participants who had uterine rupture, 88.4 females lost their fetus (β = 0.884; 95% CI: 0.827, 0.942). From 100 females who develop uterine rupture, 9.1 died (β = 0.091; 95% CI: 0.040, 0.142). From 100 females who develop uterine rupture, 97.5 developed additional obstetric complication (β = 0.975; 95% CI: 0.947, 1.000). Conclusion. Residence, ANC follow-up, and gestational age are significant determinants of uterine rupture. Fetal loss, maternal death, and obstetric complications are significant bad outcomes of uterine rupture.